The influence of drinking fluid on endurance cycling performance: A meta-analysis - Holland, J. J.; Skinner, T. L.; Irwin, C. G.; Leveritt, M. D.; Goulet, E. D. B. (Sports Medicine, 2017)
Background: Fluid replacement during cycling exercise evolves on a spectrum from simply drinking to thirst to planned structured intake, with both being appropriate recommendations. However, with mixed findings suggesting fluid intake may or may not improve endurance cycling performance (ECP) in a diverse range of trained individuals, there is a clear need for summarised evidence regarding the effect of fluid consumption on ECP. Objectives: (1) Determine the magnitude of the effect of drinking fluid on performance during cycling exercise tasks of various durations, compared with no drinking; (2) examine the relationship between rates of fluid intake and ECP; and (3) establish fluid intake recommendations based on the observations between rates of fluid intake and ECP. Study Design: Meta-analysis. Methods: Studies were located via database searches and cross-referencing. Performance outcomes were converted to a similar metric to represent percentage change in power output. Fixed- and random-effects weighted mean effect summaries and meta-regression analyses were used to identify the impact of drinking fluid on ECP. Results: A limited number of research manuscripts (n = 9) met the inclusion criteria, producing 15 effect estimates. Meta-regression analyses demonstrated that the impact of drinking on ECP under 20-33 °C ambient temperatures was duration-dependent. Fluid consumption of, on average, 0.29 mL/kg body mass/min impaired 1 h high-intensity (80% peak oxygen uptake [Vo2peak]) ECP by -2.5 ± 0.8% (95% confidence interval [CI] -4.1 to -0.9%) compared with no fluid ingestion. In contrast, during >1 to =2 h and >2 h moderate-intensity (60-70% Vo2peak) cycling exercise, ECP improved by 2.1 ± 1.5% (95% CI 1.2-2.9%) and 3.2 ± 1.2% (95% CI 0.8-5.6%), respectively, with fluid ingestion compared with no fluid intake. The associated performance benefits were observed when the rates of fluid intake were in the range of 0.15-0.20 mL/kg body mass/min for >1 to =2 h cycling exercise and ad libitum or 0.14-0.27 mL/kg body mass/min for cycling exercise >2 h. Conclusions: A rate of fluid consumption of between 0.15 and 0.34 mL/kg body mass/min during high-intensity 1 h cycling exercise is associated with reductions in ECP. When cycling at moderate intensity for >1 to =2 h, cyclists should expect a gain in performance of at least 2% if fluid is consumed at a rate of 0.15-0.20 mL/kg body mass/min. For cycling exercise >2 h conducted at moderate intensity, consuming fluid ad libitum or at a rate of 0.14-0.27 mL/kg body mass/min should improve performance by at least 3%. Until further research is conducted, these recommendations should be used as a guide to inform hydration practices.